The Neural Basis of Individual Face and Object Perception - Watson, Rebecca; Huis in ’t Veld, Elisabeth M. J.; de Gelder, Beatrice (Frontiers in Human Neuroscience, 2016)
We routinely need to process the identity of many faces around us, and how the brain achieves this is still the subject of much research in cognitive neuroscience. To date, insights on face identity processing have come from both healthy and clinical populations. However, in order to directly compare results across and within participant groups, and across different studies, it is crucial that a standard task is utilised which includes different exemplars (for example, non-face stimuli along with faces), is memory-neutral, and taps into identity recognition across orientation and across viewpoint change. The goal of this study was to test a previously behaviourally tested, optimised face and object identity matching design in a healthy control sample whilst being scanned using fMRI. Specifically, we investigated categorical, orientation, and category-specific orientation effects while participants were focused on identity processing of simultaneously presented exemplar stimuli. Alongside observing category and orientation specific effects in a distributed set of brain regions, we also saw an interaction between stimulus category and orientation in the bilateral fusiform gyrus and bilateral middle occipital gyrus. Generally these clusters showed the pattern of a heightened response to inverted, as opposed to upright faces; and to upright, as opposed to inverted shoes. These results are discussed in relation to previous studies and to potential future research within prosopagnosic individuals.